Novel structural arrangement of nematode cystathionine β-synthases: characterization of Caenorhabditis elegans CBS-1 - Vozdek, Roman; Hnízda, Aleš; Krijt, Jakub; Kostrouchová, Marta; Kožich, Viktor (Biochemical journal (London. 1984), 2012)
CBSs (cystathionine β-synthases) are eukaryotic PLP (pyridoxal 5 *-phosphate)-dependent proteins that maintain cellular homocysteine homoeostasis and produce cystathionine and hydrogen sulfide. In the present study, we describe a novel structural arrangement of the CBS enzyme encoded by the cbs-1 gene of the nematode Caenorhabditis elegans. The CBS-1 protein contains a unique tandem repeat of two evolutionarily conserved catalytic regions in a single polypeptide chain. These repeats include a catalytically active C-terminal module containing a PLP-binding site and a less conserved N-terminal module that is unable to bind the PLP cofactor and cannot catalyse CBS reactions, as demonstrated by analysis of truncated variants and active-site mutant proteins. In contrast with other metazoan enzymes, CBS-1 lacks the haem and regulatory Bateman domain essential for activation by AdoMet (S-adenosylmethionine) and only forms monomers. We determined the tissue and subcellular distribution of CBS-1 and showed that cbs-1 knockdown by RNA interference leads to delayed development and to an approximately 10-fold elevation of homocysteine concentrations in nematode extracts. The present study provides the first insight into the metabolism of sulfur amino acids and hydrogen sulfide in C. elegans and shows that nematode CBSs possess a structural feature that is unique among CBS proteins.
Keywords: Models, Molecular; biokatalýza; Molecular Sequence Data; Cystathionine beta-Synthase; Humans; Protein Structure, Tertiary; zvířata; Homocysteine; Homeostasis; Protein Structure, Quaternary; konzervovaná sekvence; cytoplazma; molekulární modely; Sequence Alignment; cystathionin-beta-synthasa; Organ Specificity; sekvence aminokyselin; sekvenční seřazení; kvarterní struktura proteinů; molekulární sekvence - údaje; orgánová specificita; Animals; Biocatalysis; Amino Acid Sequence; lidé; Cytoplasm; Caenorhabditis elegans; homocystein; homeostáza; Conserved Sequence; terciární struktura proteinů